ISTIKHDAAM TATHBIIQ MISK KAWASIITHAH LITA'LIIM AL-LUGHAH AL-ARABIYYAH FII SHOFFI ASSAABI' FII MADRASAH NAMIRA AL-MUTAWASSITHAH AL ISLAAMIYAH PROBOLINGGO - Moh. Zaini Mun'im; Mamluatun Ni'mah; Ainur Rofiq Sofa (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
Learning Arabic in the intermediate stage requires good planning so that the learning and assessment process is in line with the desired goals. This enables to improve efficiency and change students' perspectives on learning Arabic using Arabic games for Misk app. The use of educational materials for educational activities in Arabic must continue in the 5.0 era. Because this is a challenge and a need for technology. Therefore, it is necessary to develop Arabic language learning materials so that they can keep pace with scientific and technological progress, and so that learning Arabic does not become boring for students. For example, app-based learning materials are being taught, it fits perfectly with the lifestyle of millennial kids who like to watch photos, videos and even movies. The four-step method is used to make Arabic conversation easy and accessible. The first step is to listen to the Arabic language a lot, the second step is to memorize many sentences and paragraphs in the Arabic language, and the third step is to practice the Arabic language by dealing with friends or family. The fourth step is to express everything in Arabic